The influence of boccia on self-esteem and increasing the functional capabilities of disabled people - Tomasz Łosień; Anna Mędrak; Paweł Plaskacz; Izabela Bajerska; Magdalena Reut; Emilia Dragon; Martyna Polko; Aleksandra Cebula (Kazimierz Wielki University, 2018)
Sport is an important supplement to the rehabilitation process and opens the way to improving the comfort and quality of life of people with disabilities. Sport not only accelerates regenerative, adaptive and compensatory processes, but also enables the creation of new social contacts, improves self-esteem and physical performance. The precursor to the dynamic development of disabled sports was Sir Ludwig Guttmann, who changed the perception of the sport of disabled people and placed it on a par with the sport of non-disabled people. Boccia is one of the paralympic disciplines that do not have their equivalent in the Olympic program. In 1992, during the Paralympics in Barcelona, boccia became a permanent Paralympic discipline and gave the opportunity to people with the greatest disabilities of the musculoskeletal system to participate in sports competitions. Boccia got to Poland in the early 90s thanks to a group of Swedish athletes from Malmo and at that time the first boccia trainings under the supervision of Witold Maciejewski, organized by Romuald Schmidt, started in Poland.